Le Sūtra des contemplations du Buddha Vie-infinie: essai d'interprétation textuelle et iconographique - Ducor, Jérôme; Loveday, Helen (Bibliothèque de l'École des Hautes Études, Section des Sciences Religieuses, 2011)
"'Le Sūtra des contremplations du Budda Vie-Infinie' played a role in the history of the Pure Land, this tradition to this day occupies a major place in Buddhism of the Far East. Typical of the ideal of the Great Vehicle, this text provides a complex method to visualize the Buddha Amida and his kingdom in this life and a more accessible practice: the recitation of the name of the Buddha (nembutsu) to be born with him at the next life. Unknown Indian sources, but translated into Chinese in the early fifth century AD, this sermon is about fifty years since the subject of a Deat its true origin. However, it occupies a key position between the archaic Chinese translations of the Great Sutra of the arrangement of the Sukhāatī (III century) and the flowering of the school of Pure Land in the era of Tang (VII century). In addition, the Sutra contemplations stands out as an important source of the Sino-Japanese Buddhist art, from Central Asia to medieval Japan. Representations of large frescoes and painted banners of eighth and ninth centuries, discovered in the caves of Dunhuang, show a long iconographic development, including the earlier stages can be traced by archeology. The double philological and iconographic interest of this text is therefore a milestone in the investigation trying to identify the process of acclimatization on Chinese soil of this tradition came from India via the Silk Road. For the first time, this study addresses these two dimensions together, providing a detailed introduction and an annotated translation of the text, coupled with a thorough analysis of his artistic development in China to its classical representation in Japan, 'Taima Mandala'."--Translated from the publisher's website